The Development of E-Module of Hydrocarbon Material Using Lectora Inspire - Miranti, Maya; Muharini, Rini; Lestari, Ira; Erlina; Sahputra, Rachmat (Universitas Pendidikan Ganesha, 2023)
Hydrocarbon material is one of the materials in chemistry which is a problem for chemisty education students. In order to develop learning media that makes it easier for students to understand hydrocarbon, research to the development of e-modules is carried out. The goal of this research is to create an e-module of hydrocarbon material that is useful and receives positive feedback. ADDIE model consisted of analysis, design, and development was used as research and development model in this study. In total 12 students from the Chemistry Education Study Program FKIP Untan, and 32 students from the main test served as respondents. Measurement and indirect communication techniques are employed in the investigation. Feasibility evaluation sheets and response questionnaires are the instruments utilized for data collection. The results show that the e-module is highly viable, with a percentage of material feasibility 88%, linguistic feasibility 91%, technical feasibility 92%, and 95% graphic viability. In the initial experiment, the proportion of student questionnaire responses was calculated at 83%, and in the main test, it was calculated at 84%, which was deemed to be very good. E-module of hydrocarbon material using Lectora Inspire was pronouneed to be extremely feasible and received a very good reaction based on the research findings, that it can be used as a learning resource in learning hydrocarbon material to improve students’ understanding.